Dosimetric characterization of an accessory mounted mini-beam collimator across clinically beam matched medical linear accelerators. (30th January 2017) - Davis, William; Crewson, Cody; Alexander, Andrew; Kundapur, Vijayananda; Cranmer-Sargison, Gavin
Abstract: Background and Purpose. The goal of this project was the dosimetric characterization of a mini-beam collimator across three clinically beam matched medical linear accelerators (linacs). Methods and Materials. The beam quality (%DD(10)), peak-to-valley dose ratio (PVDR), collimator factor ( C F f m i n i w ), and relative output ( O F f m i n i w ) were obtained for 6 MV mini-beam collimated fields of various sizes on three clinically beam matched Varian iX medical linear accelerators. Monte Carlo simulations of the mini-beam collimated fields were used to correlate the experimental results to the accelerators' electron beam full width-half maximum (FWHM) incident on the Bremsstrahlung target. Results. The beam quality of the mini-beam collimated field on all three linear accelerators agreed with that of the open field beam to within ±1%. PVDR on the different linacs varied by up to ±8.1% from the mean. Similarly, the collimator factors varied from the mean by up to ±3.6%. However, changes in the mini-beam collimated field due to changes in collimator inclination with respect to the beam central axis or field size were consistent across the three linacs. The collimator factors of the linacs were found to decrease by up to 7.1% in response to changes in inclination of less than 0.1°, and have an inverse relationship to field size. Monte Carlo simulations indicated that the disagreement in collimator factor can be linked to variation in the spatial width of the electron beam incident on the Bremsstrahlung target. Conclusion. A mini-beam collimator has been dosimetrically characterized on three clinically beam matched medical linear accelerators. Discrepancies in the mini-beam collimated field characteristics were observed across accelerators. Monte Carlo simulation revealed that these differences were related to the linac electron beam FWHM.